Breaking the stereotype: Women with environmental food knowledge eat more than men - Rohmawati, Santi; Undarwati , Anna (Journal of Educational, Health and Community Psychology, 2025)
Non-communicable diseases (NCDs) such as obesity have increased from 14.8% to 21.8% since 2018. One of the causes of this rise in obesity is individuals taking larger portions than their ideal size. It is suspected that knowledge of environmentally friendly foods influences portion size, thereby impacting the environment. Besides knowledge of environmentally friendly foods, hunger is also predicted to play a significant role in determining portion size. Therefore, research is needed on the influence of knowledge of environmentally friendly foods and hunger on portion size. The researchers aim to investigate further the influence of knowledge of environmentally friendly foods and hunger on portion size from a gender perspective. This study uses a quasi-experimental design method with 123 participants. Data analysis uses a generalized linear model. The results of this study indicate that the interaction between gender, knowledge of environmentally friendly foods, and hunger affects portion size (p= .008), the interaction between gender and knowledge of environmentally friendly foods affects portion size (p=.005), the interaction between gender and hunger affects portion size (p=.013), and gender has a positive and significant effect on portion size (p=.012). Future research can review personal factors such as behavioral intentions, values, and attitudes. In addition, considering that portion size is an external factor that can be modified, it is necessary to educate the public about appropriate and more environmentally friendly portion sizes.